Establishing A Guideline and Decision-Making Approach For UAE Solar Assets Waste Management By Utilizing PVsyst - Khalid Ali Al, Amel (2024)
This research studies the PV solar panels waste with respect to their end-of-life EOL management for PV assets installed in a solar park in the UAE. The lack of thorough worldwide rules and frameworks that direct decision-making in connection to the disposal of photovoltaic (PV) panel waste, as well as the insufficient research on the management of such waste, are the driving forces behind this study. The study aims to address this gap by identifying the factors affecting the performance and efficiency of PV systems, specifically in UAE, a country known for its extremely hot and dry climate, and establish an evaluation approach and guidelines. PVsyst simulation software was utilized for the purpose of system performance analysis and to provide support in the decision-making process by adhering to specifically designed technical flowcharts. The fundamental performance-related parameters of the PV panels, coupled with meteorological information, were determined as important elements for assessing the general performance. The study also identified the main instruments used to make end-of-life (EOL) decisions. The results reveal that the photovoltaic (PV) system at the UAE solar park completed its end of life coupled with an 80% PR ratio sooner than anticipated, with 22 years as compared to the manufacturer's expected 25 years. This leads to the conclusion that installing photovoltaic (PV) panels in hot climates regions accelerates the degradation of the PV panels. The study provides a clear understanding of the circumstances that cause PV systems to fail earlier than expected and consequently introduce more waste to the environment.